Construction Management: Tổ chức và quản lý xây dựng - Nguyen Trong Tu (2021)
Chapter 1: Historical Perspective; Chapter 2: Overview of construction industry; Chapter 3: Construction management funtions; Chapter 4: Construction Scheduling